A cor da pele com suas diferenças - Lourdes , Dayane Freitas de; Oliveira , Elânia Aparecida da Maia; Cruz, Florisvaldo Gonçalves da; Silva , Maria Sinforosa Martin da; Dan, Marlene Amaral de Matos; Carraro, Márcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf